2018
DOI: 10.1007/s13300-018-0442-0
|View full text |Cite
|
Sign up to set email alerts
|

No QTc Prolongation with Semaglutide: A Thorough QT Study in Healthy Subjects

Abstract: IntroductionSemaglutide is a glucagon-like peptide-1 (GLP-1) analog approved for the once-weekly treatment of type 2 diabetes. The objective of this 16-week, double-blind, single-center thorough QT study was to confirm that semaglutide treatment does not prolong cardiac repolarization versus placebo. Prolongation of the QT interval is a biomarker for ventricular tachyarrhythmia.MethodsIn a parallel design, 168 healthy subjects were randomized to the treatment or placebo arms, of whom 166 were treated with subc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Most novel drugs also undergo testing for their effect on the QT interval, as QT prolongation is a marker for potential ventricular fibrillation. Compared with placebo, subcutaneous semaglutide had no effect on this ECG measure in healthy volunteers, with doses above what is used in daily practice ( 113 ).…”
Section: Adverse Effects Of Semaglutidementioning
confidence: 99%
“…Most novel drugs also undergo testing for their effect on the QT interval, as QT prolongation is a marker for potential ventricular fibrillation. Compared with placebo, subcutaneous semaglutide had no effect on this ECG measure in healthy volunteers, with doses above what is used in daily practice ( 113 ).…”
Section: Adverse Effects Of Semaglutidementioning
confidence: 99%
“…Since metformin, insulin, sulfonylureas or thiazolidinedione were marketed years before the regulations about arrhythmic safety, TQT studies did not evaluate these classic antidiabetics. On the contrary, newer drugs approved after the ICH E14 guideline, such as semaglutide, have been examined in TQT studies ( Demmel et al, 2018 ). However, evaluation of glucose lowering drugs is very challenging since, for instance, changes in blood glucose concentrations per se may correlate with prolonged QTc ( Suys et al, 2006 ).…”
Section: Safety Assessment Of Antidiabetic Drugsmentioning
confidence: 99%
“…These findings complement those of a thorough QT/QTc study with s.c. semaglutide in 168 healthy subjects [ 15 ]. In the s.c. semaglutide study, there was no prolongation of the QTc interval at a supratherapeutic dose, with the upper limits of two-sided 90% CIs of the time-matched baseline-adjusted differences between semaglutide and placebo in QTcF and QT interval corrected individually for HR (QTcI) observed to be < 10 ms at all time points.…”
Section: Discussionmentioning
confidence: 99%
“…Where possible, these guidelines recommend testing drugs at levels substantially exceeding the anticipated maximum therapeutic exposure. A previous study showed that s.c. semaglutide at supratherapeutic doses does not result in a QTc interval prolongation in healthy subjects [ 15 ]. The level of exposure achieved with s.c. semaglutide is also expected to be supratherapeutic for the oral formulation.…”
Section: Introductionmentioning
confidence: 99%